LECTIN FROM CLITOCYBE NEBULARIS FUNGUS: A NEW HISTOCHEMICAL REAGENT FOR THE INVESTIGATION OF RENAL MORPHOGENESIS AND HISTOPATHOLOGY - Амбарова, Н.О. (World of Medicine and Biology, 2015)
Having used postnatal renal morphogenesis and experimental diabetic nephropathy as test-models in rats we investigated the prospective usefulness of Clitocybe nebularis fungus lectin (CNFA) for histochemical research. It was documented possibilities of this lectin application as a specific histochemical marker of renal corpuscles and of proximal tubules brush border, for morphometric studies, as well as reliable histochemical reagent for the investigation of qualitative rearrangement of renal glycoconjugates under physiological conditions and in histopathology research. Comparison of CNFA with lectins of similar carbohydrate specificities – peanut agglutinin (PNA), soybean agglutinin (SBA), Helix pomatia agglutinin (HPA) – demonstrated certain differences in labeling, encompassing unique histochemical properties of this lectin.
Keywords: rat kidney; postnatal morphogenesis; diabetic nephropathy; lectin CNFA